Left ventricular flow patterns in healthy subjects and patients with prosthetic mitral valves: An in vivo study using echocardiographic particle image velocimetry - Faludi, Réka; Szulik, Mariola; D'hooge, Jan; Herijgers, Paul; Rademakers, Frank; Pedrizzetti, Gianni; Voigt, Jens-Uwe (The Journal of thoracic and cardiovascular surgery, 2010)
Echocardiographic particle image velocimetry is a new feature tracking–based approach to visualize and quantify left ventricular flow patterns in vivo. We investigated the potential role of this new technique by assessing vortex formations in healthy left ventricles and the effect of different types of prosthetic valves on intraventricular flow patterns and flow-mediated energy dissipation. We examined 19 patients (mean age, 57 ± 19 years; 10 women). Nine were healthy, and 10 had prosthetic mitral valves (5 had bileaflet valves, 4 had bioprostheses, and 1 had a tilting-disc valve). Boluses of left heart contrast were administered intravenously. Echocardiographic apical views were analyzed offline by using prototype software that allowed intracavitary flow to be explored and enabled calculations of energy dissipation (relative pulsatile vorticity strength and vortex pulsation correlation) by means of particle image velocimetry. In healthy hearts a vortex filling the entire ventricle stores the kinetic energy of the blood and smoothly redirects the blood to the outflow tract. In patients with prosthetic valves, completely different flow patterns were identified depending on the type, orientation, and position of the valves, as well as left ventricular geometry. Patients with prosthetic valves showed significantly higher left ventricular energy dissipation than healthy subjects (relative pulsatile vorticity strength, 2.4 ± 0.7 vs 1.6 ± 0.4 [ P < .001]; vortex pulsation correlation, 1.2 ± 0.5 vs 0.7 ± 0.2 [ P < .001]). Echocardiographic particle image velocimetry is feasible. It clearly distinguishes flow patterns in healthy hearts from those in hearts with different types of prosthetic valves. Echocardiographic particle image velocimetry offers new insights into cardiac function and might be of importance to optimize valve replacement therapy.